1994
DOI: 10.1172/jci117270
|View full text |Cite
|
Sign up to set email alerts
|

Insulin regulation of renal glucose metabolism in conscious dogs.

Abstract: Previous studies indicating that postabsorptive renal glucose production is negligible used the net balance technique, which cannot partition simultaneous renal glucose production and glucose uptake. 10 d after surgical placement of sampling catheters in the left renal vein and femoral artery and a nonobstructive infusion catheter in the left renal artery of dogs, systemic and renal glucose and glycerol kinetics were measured with peripheral infusions of 13-3Hjglucose and [2-14Cjglycerol.After baseline measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(97 citation statements)
references
References 43 publications
3
90
0
4
Order By: Relevance
“…In addition, experiments in laboratory animals and human subjects have indicated that the kidney plays an important role in glucose metabolism (25,26). Animal and human studies indicate that acute renal failure results in a reduction in the systemic removal of insulin (27).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, experiments in laboratory animals and human subjects have indicated that the kidney plays an important role in glucose metabolism (25,26). Animal and human studies indicate that acute renal failure results in a reduction in the systemic removal of insulin (27).…”
Section: Discussionmentioning
confidence: 99%
“…The renal contribution to endogenous glucose production has been a matter of much controversy [4][5][6][7][8][9][10][11][12]28]. Much of the confusion in all likelihood has arisen from the fact that measurements across the renal bed, because of the high renal blood flow of around 1 l/min, are highly susceptible to methodological imprecision as regards analysis of differences in arteriovenous glucose concentrations and dilution of tracers.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that in addition the kidney may be an important component in the regulation of intermediary metabolism, in particular glucose metabolism [4]. This renewed interest in the metabolic role of the kidney was fuelled by a study by Cersosimo et al [5] who used arteriovenous balance and isotopic dilution techniques to report that in postabsorptive dogs renal glucose utilisation and production each accounted for close to 30% of total glucose turnover in the presence of net balances close to zero. More recent studies in humans have reported that the renal contribution to postabsorptive whole-body glucose production may amount to between 15 and 30%, that glutamine appears to be an important precursor for renal gluconeogenesis and that renal glucose production increases in response to epinephrine and hypoglycaemia and decreases during insulin exposure [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…At ϳ8:00 AM, an infusion of p-aminohippuric acid (12 mg/min) was started for determination of renal blood flow (RBF). In addition, five subjects also received an infusion of [9, H]palmitate; their baseline data have been previously reported (41). Between 8:00 and 9:00 AM, a renal vein was catheterized under fluoroscopy and the position of the catheter tip ascertained by injecting a small amount of iodinated contrast material.…”
Section: Subjectsmentioning
confidence: 99%
“…However, it should be pointed out that bias in the handling of data in some of these studies (39-42, 45, 49, 50, 52) may have led to an overestimation of renal glucose release (28). Recent studies also indicate that renal release of glucose, like that of the liver, is regulated by insulin (9,40) and counterregulatory hormones (10,39,49). These findings suggest that the kidney may also be involved in postprandial glucose homeostasis.…”
mentioning
confidence: 99%